Pengaruh Model Pembelajaran Reciprocal Teaching Dalam Meningkatkan Hasil Belajar Siswa - Aswalisah Aswalisah; Syamsuria Syamsuria; Emmi Azis (Journal on Education, 2025)
This research is experimental research with a quantitative approach which aims to determine the effect of the reciprocal teaching learning model in improving student learning outcomes. The population is all class XI students of SMA Negeri 9 Bone. The sample was taken using a non-random sampling technique with the sample in this study being class XI-4. The data collection method in the research is a test instrument in the form of a pretest and posttest. Data analysis includes instrument tests in the form of Question Difficulty Level Tests and Differentiating Power Tests, and to answer the research hypothesis, Descriptive Statistical Tests and Inferential Statistical Tests are carried out using the Normality Test, T-Test (Paired Sample T-test) and N-Gain Test. The results of the research show that the Reciprocal Teaching Learning Model has a positive effect on the Economics learning outcomes of class XI-4 students at SMA Negeri 9 Bone which is in the high category at 0.72 (70%). This can be proven from the results of the hypothesis test that has been carried out, the t value is 15.126 and the t table is 2.06390, so it can be concluded that t count > t table or 15.126 > 2.06390, so H0 is rejected and H1 is accepted.